Waiting Time for Prescription Services on Social-Health-Insurance Patients at X Kendal Hospitals: Why Takes Too Long? - Astuti, Eka Kristia Ayu; Sriatmi, Ayun; Agushybana, Farid (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Excessive waiting time for prescription services at the pharmacy can negatively impact a hospital's reputation. Exceeding the minimum service standard for prescription service waiting time may indicate bottlenecks in the process, leading to inefficient service delivery.Objectives: This research aimed to determine the average waiting time for the prescription services for social health insurance patients and identify external and internal factors that prolong the prescription process.Methods: The research employed a mixed-method approach using an explanatory sequential design. Quantitative data was collected by measuring prescription waiting times from the submission of the prescription sheet by the patient to dispensing medicine to the patients. Qualitative data was gathered through in-depth interviews.Results: The results of the analysis of 100 prescriptions (38 compound and 62 non-compound) showed that the average waiting time for compound prescriptions was 50.42 minutes and 41.03 minutes for non-compound prescriptions. The longest stage in compound and non-compound prescription processes was prescription review, averaging 19 minutes from all outpatient clinic prescriptions sampels. Results of in-depth interviews revealed that incomplete prescription information by doctors, the total number of medicine items, distraction from patients, inadequate staff skills, and a shortage of prescription pharmacists contributed to delays in prescription services.Conclusion: Duration of prescription services for social health insurance that exceeded the standard time was observed in non-compound prescriptions, with bottlenecks occurring during the prescription review. Therefore, pharmacy management should evaluate and improve prescription services to enhance the efficiency of service time.